Vegetation Structure and Regeneration Studies on Two Adjacent Protected and Unprotected Tropical Forest Sites, in Central India - Lall, Jagjeevan (Indian Forester, 1990)
Present paper deals with differences in forest structure and regeneration at Bandhavgarh National Park (protected site) and Tala forest range (unprotected site). Species diversity index (H') was found to be significantly bigger at Bandhavgarh National Park site indicating species richness and their abundance. The two sites could be segregated even on the basis of differing abundances of common dominant species as revealed by Hotteling's T2 test. In general regeneration pattern of species was observed to be far better at Bandhavgarh National Park than at Tala forest. The degraded forest conditions at Tala forest are attributed to Severe biotic pressures as the forest area is open to human intereference from near by villages.